The Students’ Perception towards the Use of Padlet in L2 Writing - Susanti, Novia Indri; Ayuni, Marlinda (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2018)
The use of technology to make the learning process more interesting had become very popular. Padlet is one of the applications which have features to support the teaching and active learning activity in the classroom or even out of the classroom. It is a web-based application which enables you to write or pin up files such as pictures or video to the virtual walls on Padlet. This study discusses the using of Padlet to enhance the students’ interest in writing class and how this application can improve the students’ writing skill. This study use qualitative research and questionnaire to get the data. This study used 5 questions of questionnaire that is given after 41 students try Padlet for writing practice. The results of this study are based on students’ perception that agree that accessing and using Padlet is easy and it is more fun than traditional way, using Padlet for writing practice is interesting because of its features, and they can improve their writing skill by practicing on Padlet. The suggestion that is given is teacher should make sure there are enough facilities to make the using of Padlet effective.